Pontian District Council / Hafizah Razali - Razali, Hafizah (University Technology MARA Sarawak, 2016)
Pontian District Council was established in 01 November, 1976 under ACT 124 (Temporary Act) which was later declared as Act 171, Local Government Act 1976. This Council administration covered Bandar Pontian, Pekan Nanas, Benut, Permas and Ayer Baloi. Before the establishment of Pontian District Council, Bandar Pontian was administrated by their respective Local Councils. Since the establishment of Pontian District Council, 3 Local Council namely Pekan Nanas Local Council, Benut Local Council and Ayer Baloi Local Council along Pontian City Council was abolished and its administration was taken over by Pontian District Council.